Independently Tunable Ultrasharp Double Fano Resonances in Coupled Plasmonic Resonator System - Hongxue Fu; Shilei Li; Yilin Wang; Gang Song; Pengfei Zhang; Lulu Wang; Li Yu (IEEE Photonics Journal, 2018)
A coupled plasmonic resonator system is investigated by both the finite element method (FEM) and the multimode interference coupled-mode theory (MICMT). The resonator system is made up of a cross rectangular cavity on two metal–insulator–metal (MIM) waveguides separated by a metal baffle. The asymmetric cross rectangular in the structure induces an additional Fano resonance in the transmission spectrum, which only single Fano resonance arises in the structure consisted of the symmetric cross-rectangular cavities. The positions of double Fano resonances in the transmission spectrum can be manipulated independently by changing the size of the horizontal rectangular cavity. It is of great help for designing photonic component at fixed wavelengths. The proposed structure based on our independently tunable double Fano resonances has a wide application in the sensors, splitters, switches, and nano-photonic integrated circuits devices.